Expeditious Assembly of Fluorenones through Domino Reactions of Benzoyl Chlorides with Arylboronic Acids Catalyzed by ONO Pincer‐like Palladium(II) Complexes. Issue 20 (9th September 2016) - Vignesh, Arumugam; Kaminsky, Werner; Dharmaraj, Nallasamy
Abstract: A new set of palladium(II) complexes featuring ONO pincer‐type ligands were synthesized and utilized as efficient homogeneous catalysts for the domino reactions of benzoyl chlorides with arylboronic acids to yield a library of fluorenones. The titled reaction proceeded smoothly in H2 O/MeOH media at a low catalyst loading (0.1 mol %) under mild reaction conditions in an open flask, and the catalyst could be reused over six consecutive runs. To validate the currently developed methodology for industrial‐level applications, a gram‐scale synthesis was done. Advantageously, the present protocol does not require any external oxidant, additives, or phase‐transfer agents. Abstract : Let′s play DomONOes ! Pd II complexes featuring ONO pincer‐type ligands are synthesized and utilized as efficient homogeneous catalysts for the domino reactions of benzoyl chlorides with arylboronic acids to yield a library of fluorenones. The reaction proceeds smoothly in H2 O/MeOH media at a catalyst loading of 0.1 mol % under mild reaction conditions in an open flask, and the catalyst can be reused over six consecutive runs.